Languishing Wood Inlay Works in Punjab: Preserving the Legacy of Wood Inlay Craftsmanship in Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Man has been creative since ages. The conception of some shape or image in his mind got transformed into concrete form with the innovative activity of his head and hands resulting in a new creation called the craft to which the heart with its sensitive feelings, emotions and passions further spurred the creative hands to add curves, contours and grooves for inlaying white and colourful chips on them- thus fixing beauty to this form to produce an artful, alluring and ultimate design christened as ‘Inlay Work’. Around 3000 BC its origin lies in Egypt on wood, glass, ivory, quarty and absidian. In the 16th century in Italy at Florence, this exceptional, matchless and distinctive work was reborn. In India this creft has been mainly carried out in Rajasthan, Uttar Pradesh and Punjab. For wood inlay in Punjab Hoshiarpur, Jalandhar, Amritsar and Bhera are known for their distinct styles. Hoshiarpur with its surrounding villages and towns like Chhauni Kalan, Boothgarh, Bassi Ghulam Hussain and Adamwal became the renowned centres of this craft. Artisans experimented further, contributing to the legacy of their art to their generations to come. The Wild Life Protection Act 1989 banned the use of ivory. The Government recommended a substitute in high quality plastic in which again these artisans excelled and achieved the heights. The business flourished. But the loss of patronage, exploitation by the middlemen, the indifference of the governments, the costly raw material, shortage of wood and immigration of the artisans is giving a big jolt to this craft. Timely and suitable steps by the government, the financial help, the interest of the N.G.Os, the co-operative societies, banks and Educational Institution is the need of the day.